Correction: "On-the-fly" coupled cluster path-integral molecular dynamics: impact of nuclear quantum effects on the protonated water dimer. Issue 29 (7th August 2015) - Spura, Thomas; Elgabarty, Hossam; Kühne, Thomas D.
<x xml:space="preserve">Abstract</x> Correction for "On-the-fly" coupled cluster path-integral molecular dynamics: impact of nuclear quantum effects on the protonated water dimer` by Thomas Spura et al., Phys. Chem. Chem. Phys., 2015, 17, 14355–14359.